If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = 5(x + -5) + 7 Reorder the terms: 2 + 6x = 5(x + -5) + 7 Reorder the terms: 2 + 6x = 5(-5 + x) + 7 2 + 6x = (-5 * 5 + x * 5) + 7 2 + 6x = (-25 + 5x) + 7 Reorder the terms: 2 + 6x = -25 + 7 + 5x Combine like terms: -25 + 7 = -18 2 + 6x = -18 + 5x Solving 2 + 6x = -18 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + 6x + -5x = -18 + 5x + -5x Combine like terms: 6x + -5x = 1x 2 + 1x = -18 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + 1x = -18 + 0 2 + 1x = -18 Add '-2' to each side of the equation. 2 + -2 + 1x = -18 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -18 + -2 1x = -18 + -2 Combine like terms: -18 + -2 = -20 1x = -20 Divide each side by '1'. x = -20 Simplifying x = -20
| 1/5(x-2)-(2x-3)=2/3(4x+1)-1/6(2x+7) | | 6x-26=12+4x | | 1-7y=3-8y | | 72+80+106+4x=360 | | 4x+8=-3x-20 | | -102-10x=-2x+138 | | 6p+9=5p+17 | | Y=2(0)-9 | | -7x-11=9x+25 | | 3(2r-2)=30 | | 3x-63=45+12x | | 28=4y^2 | | 4x=x+95 | | 5-4y=2-5y | | 5y-1+2y=3 | | -46-12x=-9x+41 | | Y=17-0.5(10.5) | | -4+3x=6x-2 | | 17-2p=4p-5 | | x=-6-2y | | 26=4x+4y | | -3x-62=113+4x | | 80+42+2x=180 | | 25x+1=6252x+3 | | y=x^2-8x+25 | | 15k=(9-k)k | | 2x-1/3-x+13/24=3x+5(5x+5)/8 | | -60+11x=-5x+132 | | 3x-2(17-0.5x)=8 | | n^2+16n+52=4 | | 50=-7x+3x+2 | | 0=-20.76x+30.12 |